Emphasizing the Attitude of Caregiver and Role of Patient-centered Medical Home Concept in the Management of Natal Teeth - Bhavna Gupta Saraf; Neha Sheoran; Sfurty Prakash; Manish Shaw (Indian Journal of Dental Sciences)
The presence of natal teeth has accompanying physical difficulties such as pain on suckling, refusal to feed, irritation, and injury to the infant’s tooth. However, this condition also has a mental bearing on the patient’s family, especially the mother. Therefore, this article aims to establish a holistic approach to treat the condition both physically and psychologically, amalgamating aspects of counseling psychology, family psychology, and community psychology. It also emphasizes the importance of the patient-centered medical home concept in treating a patient with a congenital condition.